Analysis performance of database programming for computation in statistical application - Abdul Rahid @ Abdul Rashid, Nurul Najwa (2015)
Control chart is a graphical tool for monitoring and process control. This chart is widely use in Statistical Process Control (SPC) and it is used to ensure the quality of certain product and services. With the increasing amount of data in a production floor, the computation process of generating the control chart become slower. This research proposes to use database programming (stored procedures) to optimize the computation process to generate control chart application. This research is focusing on analysing the performance of database programming for computation in statistical application. The statistical method involved in this project is control charts. The research methodology for this project is experimental methodology. Two different methods of computation process to generate control charts are developed. One method is based on application programming language and the second method is based on the combination of application programming and database programming. Evaluation was based on average elapsed time taken to complete the process of computation in generating the control charts. The finding suggests that combining the application programming and the database programming can reduce the elapsed time for execution the computation process in statistical application.